SELF EFFICACY PADA ANAK TUNADAKSA : LEVEL, STRENGTH, GENERALITY - Suprihadi; Mochamad Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Self efficacy is a belief held by an individual regarding their abilities or potential, so that they can achieve the desired goals using their own means. Self efficacy owned by every individual, including disabled children. A quadriplegic child is a child who has a physical disability so that the child experiences physical problems or limitations in mobility like other people. This research aims to find out self efficacy in children with disabilities. The type of research used is qualitative research with a case study method. This research was carried out at Gunungsari Elementary School, Madiun Regency. Based on the research conducted, there are three aspects self efficacy in disabled children. First, the aspect of the task difficulty level (level) which includes behavior that is felt capable of and behavior that is avoided because it is felt to be beyond the limits of ability. Second, the aspect of strength level (strength) which includes optimism in learning and completing assignments. Third, the generalization aspect (generality) which includes self-confidence in a particular activity and self-confidence in a varied set of activities and situations. For example, in the academic field, WWN always completes the tasks given by the teacher, including smart students and in the non-academic field they still take part in PJOK learning according to their circumstances, but take part in PJOK learning only doing activities that they feel capable of. For example, in throwing a ball, continue to follow the exercise carefully with other students and avoid behavior because it is felt to be beyond your limits. When at home, he does assignments independently and is optimistic about completing assignments accompanied by his parents.